How many days until tomorrow? - Janover Caroline; Fremaux, Charlotte Murray (Bethesda, MD : Woodbine House, 2000)
Josh, who has dyslexia, spends the summer on an island off the coast of Maine and finds that he has much to prove to his gruff grandfather and his older brother.
Sequel to: Josh, a boy with dyslexia.
Keywords: Dyslexia -- Fiction; Grandfathers -- Fiction; Brothers -- Fiction; Islands -- Fiction; Maine -- Fiction